Islamic Finance Ecosystem’s Institutional Support: The Case of Kazakhstan - kuanova, laura (University of Darussalam Gontor Press, 2023)
The study applies the conceptual Islamic finance ecosystem model to overcome identified Islamic finance development challenges and obstacles by the country’s professionals’ survey. Research results show the strong and weak factors of Islamic finance and provide recommendations for institutional support of Islamic finance for Kazakhstan as an alternative source of economics in the challenging time of external political, financial, and technological threats. Furthermore, the study explores the Islamic finance social benefits designed to provide social justice and wealth creation.